Fatores humanos na arquitetura para a saúde: indicadores e percepções - Ludmila Cardoso Fagundes Mendes (2023)
The activities developed in Healthcare Establishments (HCE) tend to produce tension in employees, patients and visitors. Including human factors in HCE involves the physical and psychological well-being of individuals. The Support Design Theory (SDT) and Evidence-Based Design (EBD) present indicators for stress reduction and health promotion in hospital environments. The objective of this research was to analyze how human factors are treated in the professional practice of hospital architecture through the investigation of the application of recognized indicators in the components of SDT (sense of control; social support and positive distractions) and in EBD (daylighting). The healing purpose of HCE buildings justifies the relevance of how indicators related to these components are treated in publications of the Ministry of Health and in building evaluation systems. From the synthesis of the indicators identified, the method included the application of a questionnaire; the selection of more relevant indicators; the application of these indicators in a case study; the analysis of the applicability of these indicators; and proposals to fill recognized gaps in the evaluation of indicators. The result of the questionnaire pointed to daylighting as the component of greatest relevance for human well-being. Twenty-two well-being indicators related to SDT components or daylighting were identified as an element of EBD. Of these,10 were selected for analysis: individual control of artificial lighting; living areas, rest and canopy for employees; privacy; accessible gardens; areas or gardens for coexistence; comfortable waiting areas; accommodation for companions; interview room; quality views and daylight provision. The case study included the application of the indicators in an intensive care unit and in a clinical inpatient unit of a general hospital. Of the selected indicators, the case study fully met 56%, partially to 28% and didn’t meet 17%. It is believed that the main barriers to the application of well-being indicators are associated with the decisions made in the stages of elaboration of architectural projects of HCE. The research showed the relevance of a needs program for HCE buildings, which goes beyond the requirements of RDC 50/2002.